2010
DOI: 10.1002/mnfr.200900288
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and antigenotoxic properties of vegetables and dietary phytochemicals: The value of genomics biomarkers in molecular epidemiology

Abstract: There is considerable evidence that consumption of fruits and vegetables may contribute to the prevention of cancer. It is however remarkable that evidence for such a preventive action arising from mechanistic studies is becoming stronger, whereas results of some recent prospective studies are less convincing. This apparent discrepancy may be overcome, or at least understood, by introducing molecular markers in future epidemiological studies, taking modulation of molecular processes as well as genetic variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 65 publications
1
23
0
Order By: Relevance
“…Using a metabolic approach, antioxidant supplementation in smokers was found to alter lipid profiles in plasma in a manner consistent with reductions in oxidative stress [37]. However, disease outcome antioxidant clinical trials have provided less-than enthusiastic results and the ability of oral antioxidants to be absorbed and effectively reach target organs remains an area of active investigation [38]. Such studies have not been conducted in former smokers, who are at lower risk than smokers but still maintain a higher risk than nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…Using a metabolic approach, antioxidant supplementation in smokers was found to alter lipid profiles in plasma in a manner consistent with reductions in oxidative stress [37]. However, disease outcome antioxidant clinical trials have provided less-than enthusiastic results and the ability of oral antioxidants to be absorbed and effectively reach target organs remains an area of active investigation [38]. Such studies have not been conducted in former smokers, who are at lower risk than smokers but still maintain a higher risk than nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant supplements altered plasma lipid profiles in smokers in a manner consistent with the reduction in oxidative stress [31]. However, disease outcome of antioxidant clinical trials have provided less than anticipated results [32], and meta-analyses of randomized controlled trials for high doses of antioxidants except polyphenols found no overall relationship between the consumption of antioxidant supplements and cancer risk [13].…”
Section: Anthocyanin Supplements Increase Oxidative Stress In Young Hmentioning
confidence: 99%
“…The mechanisms by which fiber in general and proanthocyanidins in particular exert their effects are largely unknown (9) and any insight into the action of such preventive agents will help to clarify their role in living organisms. We hypothesized that GADF may induce a protective gene expression profile in the colon.…”
Section: Introductionmentioning
confidence: 99%